2014
DOI: 10.1111/maec.12137
|View full text |Cite
|
Sign up to set email alerts
|

Population biology and secondary production of the harvested clam Tivela mactroides (Born, 1778) (Bivalvia, Veneridae) in Southeastern Brazil

Abstract: The population structure, growth and production of the trigonal clam Tivela mactroides were investigated by monthly sampling between January 2003 and October 2004 in two areas (southern and northern) of the intertidal and subtidal zones of Caraguatatuba Bay, Southeastern Brazil. Intertidal sampling was carried out in each area along eight transects perpendicular to the shoreline. In the subtidal zone of both areas, one 50-m dredging was performed along five sampling stations arranged on three transects perpend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
0
19
0
3
Order By: Relevance
“…The data presented here indicate that a management strategy based on the reproductive pattern of this population of T. mactroides would not be viable, since it is difficult to identify a specific period when spawning is more intense. Although we recorded periods of greater maturation during winter and spring, a study of the population dynamics of the species (Turra et al 2014b) showed that this venerid recruits almost continuously through the year. However, this situation may result from other factors such as reduced predation pressure or even better environmental conditions (e.g.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The data presented here indicate that a management strategy based on the reproductive pattern of this population of T. mactroides would not be viable, since it is difficult to identify a specific period when spawning is more intense. Although we recorded periods of greater maturation during winter and spring, a study of the population dynamics of the species (Turra et al 2014b) showed that this venerid recruits almost continuously through the year. However, this situation may result from other factors such as reduced predation pressure or even better environmental conditions (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…Considering the maturation pattern of the females, the increase in the gametogenesis in T. mactroides during winter and spring suggests a slight summer-autumn spawning intensification. However, given the existence of constant recruitment events during the year in Caraguatatuba Bay (Turra et al 2014b), spawning may also occur in other periods, although with less intensity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Latitudinal differences in life history traits have been described for several bivalves, such as Donax hanleyanus (Cardoso & Veloso 2003;Herrmann et al 2009) and Tivella mactroides (Turra et al 2014), and are likely to affect the reproduction of A. brasiliana as well (Grotta & Lunetta 1982). All studies that analyzed the reproductive biology of A. brasiliana in tropical regions (sensu Spalding et al 2007) have reported no resting period (Table 1), whereas a resting stage was detected at Araçá (this study) and in the state of Santa Catarina (Araújo 2001), which is the southernmost location where the reproduction of A. brasiliana has been investigated.…”
Section: Latitudinal Patternsmentioning
confidence: 98%
“…Estes moluscos são comumente capturados pela população local para o consumo próprio, sendo a sua captura predominantemente realizada por mulheres. Esses bivalves formam densas populações, o que os torna susceptível a pesca (Ocaña, 2015;SilvaCavalcanti & Costa, 2011;Turra et al, 2014).…”
Section: Bivalvesunclassified